An implementation approach to rotation programs - Ville Korpela; Michele Lombardi; Riccardo D. Saulle (Aboa Centre for Economics (ACE), 2021)
We study rotation programs within the standard implementation framework under complete information. A rotation program is a myopic stable set whose states are arranged circularly, and agents can effectively move only between two consecutive states. We provide characterizing conditions for the implementation of efficient rules in rotation programs. Moreover, we show that the conditions fully characterize the class of implementable multi-valued and efficient rules.
Keywords: C71; D71; D82; 330; Rotation Programs; Job Rotation; Assignment Problems; Implementation; rights structures; Stability